2021
DOI: 10.1002/ecy.3437
|View full text |Cite
|
Sign up to set email alerts
|

Semiarid grasslands and extreme precipitation events: do experimental results scale to the landscape?

Abstract: The frequency and magnitude of deluges (extremely large rain events) are increasing globally as the atmosphere warms. Small-scale experiments suggest that semiarid grasslands are particularly sensitive to both the timing and size of deluge events. However, the assumption that plot-scale results can be extrapolated across landscapes with variable soil textures, plant communities, and grazing regimes has seldom been tested, despite being key to forecasting regional consequences of precipitation extremes. We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…S1: Source LULC polygon classes, levels, numbers and total area for Orbroich; Table S2: Source grassland polygon statistics for Wahnbachtal; Table S3: Year, season and number of images used in analysis for Orbroich and Wahnbachtal sites; Table S4: Correlation of various vegetation indices (Vis) considered for the study; Table S5: Evaluation of cluster separability of selected VIs using transformed divergence; Parcel classes used for grassland analysis are in bolded black font; Table S6: Comparison of cluster assignments using NDVI, MSI, and TVI vegetation indices for Orbroich and Wahnbachtal sites showing agreement between methods in grey shaded cells. References [9,10,[31][32][33] are cited in the Supplementary Materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S1: Source LULC polygon classes, levels, numbers and total area for Orbroich; Table S2: Source grassland polygon statistics for Wahnbachtal; Table S3: Year, season and number of images used in analysis for Orbroich and Wahnbachtal sites; Table S4: Correlation of various vegetation indices (Vis) considered for the study; Table S5: Evaluation of cluster separability of selected VIs using transformed divergence; Parcel classes used for grassland analysis are in bolded black font; Table S6: Comparison of cluster assignments using NDVI, MSI, and TVI vegetation indices for Orbroich and Wahnbachtal sites showing agreement between methods in grey shaded cells. References [9,10,[31][32][33] are cited in the Supplementary Materials.…”
Section: Discussionmentioning
confidence: 99%
“…Figure S5: Two-stage method of image normalization showing the master base image (dark orange) and base images for each year (light orange), and within-year images normalized to the base image for that year (each row) for the Orbroich study site; Figure S6: Grassland clusters (left) with temporal adjustment to account for annual factors affecting entire areas (center) resulting in final annual NDVI values for each cluster (right) in Orbroich (top) and Wahnbachtal (bottom); Figure S7: Comparison of clustering using all available images across each year (A) and only the spring base image (B) for the Orbroich site; Figure S8: Statistical analysis of cluster; Figure S9: Cluster variability for Orbroich site using the standard deviation of individual grassland parcel NDVI values for each year; Figure S10: Cluster variability for Wahnbachtal site using the standard deviation of individual grassland parcel NDVI values for each year; TableS1: Source LULC polygon classes, levels, numbers and total area for Orbroich; TableS2: Source grassland polygon statistics for Wahnbachtal; TableS3: Year, season and number of images used in analysis for Orbroich and Wahnbachtal sites; TableS4: Correlation of various vegetation indices (Vis) considered for the study; TableS5: Evaluation of cluster separability of selected VIs using transformed divergence; Parcel classes used for grassland analysis are in bolded black font; TableS6: Comparison of cluster assignments using NDVI, MSI, and TVI vegetation indices for Orbroich and Wahnbachtal sites showing agreement between methods in grey shaded cells. References[9,10,[31][32][33] are cited in the Supplementary Materials.…”
mentioning
confidence: 99%
“…To assess plant growth and phenology, weekly plot canopy greenness was estimated using repeat digital photography (adapted from Post & Knapp, 2020, 2021). Previous research has demonstrated that plot‐level responses in canopy greenness scale well to landscape‐level measurements (e.g., satellite‐derived greenness via normalized difference vegetation index, or NDVI; Post et al, 2021). For each photograph, a digital camera was positioned directly over a marked region of interest (50 × 50 cm frame in the corner of each plot) at a 90° angle relative to the ground surface.…”
Section: Methodsmentioning
confidence: 98%